Aligner Technology in open bite treatment: Teknologi Aligner pada perawatan gigitan terbuka - Eka Erwansyah; Burhanuddin Daeng Pasiga; Rika Damayanti; Muh Rahmanrahim Burhanuddin (Makassar Dental Journal PDGI Makassar, 2021)
Background: Clearaligner or invisalign is an orthodontic device that uses a gradual transparent aligner to align teeth position. This device is used as an alternative treatment to dental braces. The development of clear aligner technology has increased for the treatment of complex cases. Clear aligners provide an aesthetic and comfortable treatment experience, facilitate oral hygine treatment, cause less pain than conventional orthodontic appliances, and reduce the number and duration of visits. However, production costs, dependence on patient cooperation and the inability to treat certain malocclusions are the limitations of this clear aligner treatment. Conclusion: Clear aligners are an aesthetically pleasing and comfortable orthodontic treatment option for patients, but there are still few reviews or studies that have looked at this relatively new type of orthodontic treatment. In addition, although this aligner treatment in some literature states contraindicated in open bite cases, however, through the use of an additional device, the attachment to this device is able to provide the effect of intrusion of the anterior teeth and extrusion of the posterior teeth for the anterior open bite case.